2003
DOI: 10.1177/0091270003257456
|View full text |Cite
|
Sign up to set email alerts
|

The Antiparasitic Moxidectin: Safety, Tolerability, and Pharmacokinetics in Humans

Abstract: A study in healthy male volunteers was completed to evaluate the safety, tolerability, and pharmacokinetics of a single oral dose of the antiparasitic moxidectin (MOX). This drug is registered worldwide as a veterinary antiparasitic agent for use in companion and farm animals. This is the first study of MOX in humans. All subjects were between the ages of 18 and 45 years, with normal cardiac, hematologic, hepatic, and renal function. Doses of MOX studied were 3, 9, 18, and 36 mg in cohorts of 6 subjects each (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
131
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(141 citation statements)
references
References 36 publications
8
131
1
1
Order By: Relevance
“…In fact, both ivermectin (Fig. 1A) (7) and its analogue, moxidectin (30), were originally marketed as veterinary anthelmintics (20). Ivermectin targets the O. volvulus microfilariae and has an embryostatic effect on the adult female worms (8,31).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, both ivermectin (Fig. 1A) (7) and its analogue, moxidectin (30), were originally marketed as veterinary anthelmintics (20). Ivermectin targets the O. volvulus microfilariae and has an embryostatic effect on the adult female worms (8,31).…”
Section: Discussionmentioning
confidence: 99%
“…New classes of cysteine protease inhibitors are being developed as anthelminthic and antiprotozoal drugs (163), and other studies have indicated the efficacy of triclabendazole for infection with the difficult to treat liver fluke Fasciola hepatica (164,165). Human and animal studies also suggest that tribendimidine will prove effective against food-borne flukes (166) and the drug moxidectin might become an alternative to ivermectin for the treatment of filarial infections (167). Finally, based on the observation that the filarial parasites Wuchereria bancrofti and Onchocerca volvulus harbor bacterial endosymbionts of the genus Wolbachia and depend on these endosymbionts for normal metabolic and reproductive activities, there is excitement about the development and use of antibiotics to target adult filarial worms (168).…”
Section: Global Control Of Helminthiases and Clinical Research Imperamentioning
confidence: 99%
“…For human scabies, ivermectin is the only licensed oral acaricide, with moxidectin under recent consideration for development as an alternative to ivermectin (1). As moxidectin has a prolonged plasma half-life (t 1/2 ) in humans (29 to 47 days versus 14 h) (2)(3)(4), it is anticipated that it may be more suitable than ivermectin as a single oral dose, providing coverage over the entire mite life cycle.…”
mentioning
confidence: 99%